2017
DOI: 10.1007/s00198-017-4239-1
|View full text |Cite|
|
Sign up to set email alerts
|

Subsequent fracture risk of women with pregnancy and lactation-associated osteoporosis after a median of 6 years of follow-up

Abstract: Almost a quarter of patients with PAO will sustain a subsequent fracture, and this fracture risk correlates with the number of fractures at time of diagnosis. Patients with PAO need to be informed about their potential subsequent fracture risk before deciding for further pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
1
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 27 publications
2
58
1
11
Order By: Relevance
“…(11,(15)(16)(17)(18)(19) In two cohort studies (n = 35 and n = 107), (20,21) over 80% had no known cause, (20) 70% were primiparous, (20,21) and 89% to 93% presented with vertebral fractures. (20,21) BMD before pregnancy is usually not available because there would have been no indication to measure it. BMD by DXA at presentation is generally extremely low, (13,(16)(17)(18)(19)(22)(23)(24)(25)(26)(27)(28)(29) with reported Z-scores often below -3.0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(11,(15)(16)(17)(18)(19) In two cohort studies (n = 35 and n = 107), (20,21) over 80% had no known cause, (20) 70% were primiparous, (20,21) and 89% to 93% presented with vertebral fractures. (20,21) BMD before pregnancy is usually not available because there would have been no indication to measure it. BMD by DXA at presentation is generally extremely low, (13,(16)(17)(18)(19)(22)(23)(24)(25)(26)(27)(28)(29) with reported Z-scores often below -3.0.…”
Section: Introductionmentioning
confidence: 99%
“…Most women are otherwise healthy, with no known condition that would predispose them to fractures. (11,(15)(16)(17)(18)(19) In two cohort studies (n = 35 and n = 107), (20,21) over 80% had no known cause, (20) 70% were primiparous, (20,21) and 89% to 93% presented with vertebral fractures. (20,21) BMD before pregnancy is usually not available because there would have been no indication to measure it.…”
Section: Introductionmentioning
confidence: 99%
“…However, multiple vertebral fractures may lead to severe back pain and height loss, reducing the quality of life, and result in a residual risk of subsequent fracture, which might require medical intervention . Furthermore, a recent large cohort study reported that 24.3% of 107 patients with PLO had one or more subsequent fractures during a median follow‐up of 6 years . The risk was positively correlated with the number of fractures at the time of diagnosis, suggesting that severe PLO carries a substantial risk of fracture, which must be taken into consideration …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent large cohort study reported that 24.3% of 107 patients with PLO had one or more subsequent fractures during a median follow‐up of 6 years . The risk was positively correlated with the number of fractures at the time of diagnosis, suggesting that severe PLO carries a substantial risk of fracture, which must be taken into consideration …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the administration of denosumab can significantly improve patients' symptoms and bone density [12]. Stopping breastfeeding could reduce the loss of calcium, and the longer of the lactation lasting, the more fractures occur on average [13]. Bisphosphonates have a relatively short bone retention time and are highly effective and well tolerated in the treatment of PLO, but they need to be cautious or stop breastfeeding because of their potential harm to the fetus [14,15].…”
Section: Discussionmentioning
confidence: 99%